Penguatan Komunikasi Dasar dan Edukasi Seksual pada Anak Sekolah Dasar melalui Program: ‘Aku Berani Bicara’ - Budi Rahayu, Pramudita; Pramudita (Journal Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Children in elementary school are at a crucial phase in developing self-understanding, communication skills, and awareness of their body's boundaries. Lack of age-appropriate sexual education and poor basic communication skills can increase the risk of children experiencing violence or abuse, as well as making it difficult to communicate their experiences. A community service program called “Aku Berani Bicara” (I Dare to Talk) is a preventive measure that aims to improve basic communication skills and provide safe, child-friendly, and developmentally appropriate sexual education. This activity was carried out with a participatory and interactive approach in one of the elementary schools in Tamangapa Raya, Tamangapa Urban Village, Manggala District, Makassar City, involving teachers, as well as grade V students. Activities consisted of educational sessions, simulations, role plays, and training for educators and students to support consistency of messages in the home and school environment. Evaluation showed an increase in children's understanding of their body rights, ability to say “no”, and confidence to talk to adults they trust when facing uncomfortable situations. The program emphasized how important it is to.